Perlakuan Akuntansi dalam Pengelolaan Piutang Dagang pada Transaksi Penjualan Kredit: Studi pada Pedagang Grosir Skala Menengah - Ilham Pajar Asidiq, Wizhar; Noor Sayuti, Muhammad; Mubarok, Arif (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The purpose of this research is to analyze the accounting practices applied in the recording and reporting of accounts receivable on credit sale transactions by medium-sized wholesalers and to determine the extent to which these accounting implementations contribute to the management of accounts receivable in order to maintain cash flow and operational stability of the business. This study employs field research with a descriptive qualitative approach, aiming to explore the accounting practices of accounts receivable in credit sale transactions among medium-sized wholesalers in Sembuluh Village, Central Kalimantan. The subjects of the research were determined through purposive sampling, namely wholesalers who apply a credit sales system and are directly involved in recording accounts receivable. Data were collected through observation, interviews, and documentation, which were then validated using triangulation techniques. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data collection, reduction, presentation, as well as conclusion drawing and verification. The research results indicate that the practice of accounting for accounts receivable among medium-sized wholesale traders in Sembuluh Village is still carried out manually and simply. Record keeping is done without using a computer system, relying only on receipts and notebooks, and is not organized in a regular manner or according to accounting standards. Although this recording is useful for identifying customers in debt and billing schedules, the limitations in the recording system and the absence of formal financial reports result in ineffective management of receivables, which does not support cash flow continuity and business stability.